2018
DOI: 10.1002/chem.201705560
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Porous Carbazole‐Decorated Copolymer Monodisperse Microspheres: Facile synthesis, Selective and Recyclable Detection of Iron (III) in Aqueous Medium

Abstract: We demonstrate an environmentally friendly one-step soap-free emulsion polymerization strategy to develop fluorescent carbazole-based copolymer monodisperse microspheres for highly sensitive and selective detection of Fe . The copolymer microspheres feature a stable spherical morphology with a narrow size distribution through regulating N-vinylcarbazole (NVCz) content (1.25-10.0 wt.%). Notably, the as-made microspheres exhibit a strong luminescence, tunable emission intensity and specific surface areas. Intere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Besides, surfactant-free emulsion polymerization and reverse phase microemulsion polymerization are also utilized to prepare fluorescent polymer particles. [32,47,48] For example, Roghani-Mamaqani and co-workers fabricated functionalized latex particles bearing fluorochromic and photochromic compounds by surfactant-free emulsion copolymerization of MMA and spiropyran monomers. [47] The functionalization of latex particles was achieved by adding hydroxyethyl methacrylate (HEMA), GMA and methacrylic acid (MAA) monomers.…”
Section: Emulsion Polymerizationmentioning
confidence: 99%
“…Besides, surfactant-free emulsion polymerization and reverse phase microemulsion polymerization are also utilized to prepare fluorescent polymer particles. [32,47,48] For example, Roghani-Mamaqani and co-workers fabricated functionalized latex particles bearing fluorochromic and photochromic compounds by surfactant-free emulsion copolymerization of MMA and spiropyran monomers. [47] The functionalization of latex particles was achieved by adding hydroxyethyl methacrylate (HEMA), GMA and methacrylic acid (MAA) monomers.…”
Section: Emulsion Polymerizationmentioning
confidence: 99%
“…[41] PCz is preferred especially in applications such as nano devices, rechargeable batteries and electrochemical transistors due to its very good optoelectronic properties, high charge carrier mobility, excellent morphological stability and electrochromic properties. [42] Although there are many studies on the polymerization of Cz by chemical [43] and electrochemical [44] methods, photochemical, [45,46] microwave-assisted, [47,48] emulsion, [49] addition, [50] plasma [51] and solid-state [52] polymerizations, no solid-state polymerization assisted with ultrasound and pressure has been found. Jadoun et al were reported Cz polymerization in an aqueous solution of naphthalene sulfonic acid in the presence of FeCl 3 at room temperature by ultrasound-assisted method.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are many studies on the polymerization of Cz by chemical [43] and electrochemical [44] methods, photochemical, [45,46] microwave‐assisted, [47,48] emulsion, [49] addition, [50] plasma [51] and solid‐state [52] polymerizations, no solid‐state polymerization assisted with ultrasound and pressure has been found.…”
Section: Introductionmentioning
confidence: 99%
“…Nano/microspheres have drawn a great deal of interest in immunoassays due to their key advantageous features including (i) amenability to screening and multiplexing; (ii) significantly larger specific surface area in comparison with two-dimensional (2D) platforms which facilitate higher analyte-surface interaction; and (iii) high spatial freedom for interaction with biomolecules of interest [13][14][15][16][17][18][19][20][21]. miRNA detection using different particle types are reported in the literature [22,23].…”
Section: Introductionmentioning
confidence: 99%